Tanjak Lobam Service Innovation for Regional Tax Compliance in Bintan Industrial Estate - Yuri Aditya Surya; Fitri Kurnianingsih; O. Okparizan (Manunggal Halim Jaya, 2026)
This study analyzes the service innovation of the Tanjak Lobam Tax Compliance Movement (Gerakan Taat Pajak Lobam) implemented in the Bintan Industrial Estate (Bintan Inti Industrial Estate/BIIE), Bintan Regency, using Everett M. Rogers’ (2003) Diffusion of Innovations theory, which consists of five key attributes: relative advantage, compatibility, complexity, trialability, and observability. This research employs a qualitative approach with a case study design. Data were collected through in-depth interviews with officials from the Bintan Regional Revenue Management Unit (UPTD PPD Bintan), representatives of industrial companies, and workers in the BIIE area, supported by field observations and document analysis. The findings indicate that the Tanjak Lobam innovation demonstrates a strong relative advantage, as it improves time efficiency, reduces transaction costs, and accelerates administrative processes for Motor Vehicle Tax (Pajak Kendaraan Bermotor/PKB) and Heavy Equipment Tax (Pajak Alat Berat/PAB). In terms of compatibility, the innovation aligns well with the characteristics of an industrial estate that requires flexible services without disrupting production activities. Regarding complexity, initial challenges were identified in data integration and system adaptation; however, these were gradually resolved through intensive socialization and field assistance provided by tax officers. In terms of trialability, the implementation was conducted in stages through limited trials and pilot projects, which strengthened user acceptance. Meanwhile, the observability aspect is reflected in tangible outcomes, such as improved tax compliance, reduced arrears, and changes in vehicle administration behavior within the industrial environment. The study concludes that the Tanjak Lobam initiative is an effective public service innovation that has been successfully adopted by various stakeholders because it fulfills all innovation attributes proposed by Rogers (2003). Furthermore, this innovation not only enhances regional tax service performance but also strengthens collaboration among local government, industrial actors, and workers within an industrial estate-based tax governance system.